Condom Use Consistency and Associated Factors Among College Student Men Who Have Sex with Men from Seven Colleges in Changsha City: A Cross-Sectional Survey - Wang H (Dove Medical Press, 2021)
Honghong Wang,1,* Simin Yu,1,* Wendy Cross,2 Louisa Lam,2 Biswajit Banik,2 Kaili Zhang3 1Xiangya School of Nursing, Central South University, Changsha City, 410000, Hunan Province, People’s Republic of China; 2School of Health, Federation University, Berwick, 3806, Victoria, Australia; 3School of Nursing, Xuzhou Medical University, Xuzhou City, 221004, Jiangsu Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kaili ZhangNursing School of Xuzhou Medical University, 209 Tongshan Road, Xuzhou, 221004, Jiangsu, People’s Republic of ChinaTel/ Fax +86-516-83262165Email xiaokai20060@xzhmu.edu.cnBackground: College student men who have sex with men (MSM) are at high risk for HIV infection due to multiple social and behavioral factors. Consistent condom use is nationally advocated for HIV prevention. This study explored the sexual behaviors and factors associated with condom use consistency in the past six months among college student MSM from seven colleges in Hunan Province, China.Methods: A cross-sectional survey was conducted from September 2017 to March 2018. Condom use consistency, sexual behaviors, HIV testing performance, substance use, and alcohol consumption were examined using researcher-created questionnaires. Condom use self-efficacy and HIV-related knowledge were assessed using the Condom Use Self-Efficacy Scale and the unified National AIDS Sentinel Surveillance Questionnaire. Univariate and multivariate logistic regressions were used. P < 0.05 was considered significant.Results: In the 214 respondents, the rate of consistent condom use was 56% (n = 119) during the past six months. Participants who were studying at first-tier universities (odds ratio [OR]: 2.522, 95% confidence interval [CI]: 1.255– 5.067) and had higher scores for condom use self-efficacy (OR: 2.617, 95% CI: 1.462– 4.685) were more likely to report consistent condom use than the others. The risk factor was having suspicious symptoms of sexually transmitted diseases (OR: 0.357, 95% CI: 0.163– 0.780).Conclusion: Numerous students were at high risk of HIV infection with inconsistent condom use. Comprehensive and specific topics about safe sex education from parents and peers should be offered on campuses in China.Keywords: college student men who have sex with men, condom use consistency, sexual behaviors, sex education